Proceedings of the 6th International Driving Symposium on Human Factors in Driver Assessment, Training, and Vehicle Design : Dr 2011
DOI: 10.17077/drivingassessment.1433
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Riding Experience on Glance Behavior, Brake Response Time and Deceleration Rates by Drivers and Motorcyclists

Abstract: The focus of the research was to address the crash avoidance behaviors of drivers versus motorcyclists. Avoidance tasks include, attention maintenance and hazard anticipation measured with glance behaviors, and hazard mitigation measured with response times and deceleration. Specifically, where might the driver behavior be similar or different than that of a motorcyclist? The performances of 23participants were analyzed while they drove a car and rode a motorcycle over the same low-volume, open roads. Particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…A survey by VicRoads (2009) found significant differences in the attitude towards road users among drivers and riders as well as different perception on crash risk. In a naturalistic study by Muttart et al (2011) to compare drivers' and riders' behaviour, the latter were found to have less glancing time and less number of glancing toward the road and traffic than the former and thus were more exposed to risk.…”
Section: Introductionmentioning
confidence: 99%
“…A survey by VicRoads (2009) found significant differences in the attitude towards road users among drivers and riders as well as different perception on crash risk. In a naturalistic study by Muttart et al (2011) to compare drivers' and riders' behaviour, the latter were found to have less glancing time and less number of glancing toward the road and traffic than the former and thus were more exposed to risk.…”
Section: Introductionmentioning
confidence: 99%